Implementation of the Value of Divinity in Pancasila to Strengthen Disciplinary Character at SMP Negeri 4 Banyuwangi - Siti Husnatul Maroya; Andika Ronggo Gumuru; Desi Yunita Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the implementation of the value of divinity in Pancasila to strengthen students' disciplinary character at SMP Negeri 4 Banyuwangi. The research aims to describe the implementation process, identify the obstacles encountered, and explain the efforts made by the school. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation involving the principal, vice principal for student affairs, teachers, guidance and counseling teachers, and students. The findings show that the value of divinity is implemented through religious habituation activities, including communal prayers, recitation of the Asmaul Husna, Qur’an recitation, congregational dhuhr prayers, Jumat Taqwa, Ramadan religious camps, religious holiday commemorations, and tolerance practices. The main obstacles include low student awareness, environmental influences, social media, and limited parental supervision. The school addresses these challenges through teacher role modeling, counseling services, personal guidance, educational sanctions, and collaboration with parents. Overall, these efforts effectively strengthen students' disciplinary character.